Knowledge, Attitudes, Practices, and Acceptance of Gynecologic Cancer Patients Toward Covid-19 Vaccine in Thailand: A Multicenter Cross-sectional Study - Suprasert, Prapaporn; Chuenchitkultavorn, Varisa; Phianpiset, Rattiya; Rattanaburi, Athithan; Aue-Aungkul, Apiwat; Vutibenjarasamee, Kitiya; Kolaka, Warangkana (Biomedical Sciences and Clinical Medicine, 2023)
OBJECTIVE To evaluate the knowledge, attitudes, practices (KAP), and acceptance of gynecologic cancer patients from the 4 regions of Thailand related to the COVID-19 vaccine. METHODS Gynecologic cancer patients from Chiang Mai University Hospital, Khon Kaen University Hospital, Khon Kaen Hospital, Prince of Songkhla University Hospital, and the National Cancer Institute (NCI) in Bangkok were surveyed using a WHO survey instrument. RESULTS Between February and September 2022, 1,263 patients partici- pated in this project of whom 1,084 (85.8%) had received the COVID-19 vaccine. The highest rate of vaccination was the NCI followed by Khon Kaen, Chiang Mai, and Songkhla. Of the participants, 28.2% were infected with COVID-19 and 12.9% of the infected participants were unvaccinated. Regarding KAP, the average scale level of overall participants reported ease in obtaining health literacy, a moderate probability of having severe COVID-19 infection, knowledge and adoption of proper appropriate behavior for the prevention of COVID infection, little stress regarding possible COVID-19 infection, and quite a lot of a significant level of trust in healthcare workers. Most participants generally agreed with the lifting of some regular rules to reduce the risk of infection and often many expressed a feeling of general well-being. The significantly different levels of rating scale by unvaccinated and vaccinated participants in the key areas were as follows: (Patients rated each of the areas investigated on a scale of 0 to 6, with 0 indicating lowest level of agreement/acceptance and 6 indicating the highest level) health ministry recommendations (3.92 vs. 4.16), ease of getting the COVID vaccine (3.6 vs. 3.9), “no need to receive the vaccine due to the disease being rare” (2.6 vs. 2.2), “stress made me not want to get vaccinated” (2.6 vs. 2.1), “if everyone is vaccinated, no need for me to vaccinate” (2.5 vs. 1.9), and the importance of COVID-19 vaccines (3.7 vs. 4.2). CONCLUSIONS Most gynecologic cancer patients from the 4 regions of Thailand had received the COVID-19 vaccine and exhibited good knowledge, attitudes, and practices related to this pandemic.